The Psychosocial Factors that Influencing Antiretroviral Treatment Adherence - Liranso, Gebreyohannes Selamu; Mohan, S. Singhe; Eyerus, Assefa (Journal of Clinical Research In HIV AIDS And Prevention, 2017)
The socio-cultural context of illness has become a major research area, and it has made significant contributions to our understanding of the socio-cultural dimensions of illness. In this article, we briefly trace the roots of a socio-cultural approach to illness, and we present some of the key findings of socio-cultural organized under main themes. Adherence to antiretroviral therapy drugs in the treatment of HIV infection is complicated because of many psychosocial factors. The aim of the study was to investigate the psychosocial factors involved in non-compliance with ART among people infected with HIV in Alert Hospital in Ethiopia. To achieve its objective, the study utilized a qualitative method to gather direct, inductive and wealthy information from the participants. The study covered interviews with twenty participants. The participants were selected using purposive sampling technique. The collected data was categorized and analyzed thematically based on the research objective. The results of the study indicated that the major psychological and social factors such as stigma and discrimination, social support, substance abuse, subjective norms, belief system and perceived behavioral control, and various cultural factors may uniquely contribute to deeper and potential barriers to ART adherence. Evaluating changes in the level of knowledge health workers trained in adherence measurements and concerned bodies work for providing relevant and updated information about ART issues for the followers in a convincing way. Therefore, the study has concluded that health workers in all facilities that provide ART would be trained in adherence counseling through formal training.
Keywords: Antiretroviral Therapy; Treatment; Adherence and Psychosocial Factors